The mist thief - Andrews, L J (Andrews, L J. Ever Seas, 2025)
"The third in the TikTok sensation Ever Seas series, now in a special print edition! She tried to kill him, so he made her his wife. Skadi first met her husband-to-be with blades in hand on the opposite side of a battle. She lost, and he claimed his prize. To her horror, the king of the shadow elven agrees to marry her off to Jonas, a prince in the fae realms, as a way to unite their kingdoms against a shared enemy-the light elves. Skadi knows the marriage is nothing but a political game. Feelings won't come into play. Except her new husband makes not falling in love . . . challenging. When new threats arise, Skadi must decide to either love her enemy or keep him alive by betraying him to another"--